"If We Don't Produce, Bring Another:" Work Organization and Tomato Worker Health. Issue 3 (2nd July 2020) - Kelley, Rachel I.; Ivey, Susan L.; Silver, Ken; Holmes, Seth M.
ABSTRACT: Objectives : Specific work processes and management structures that contribute to high rates of occupational illness and injury in agricultural industries are not well described in academic literature. This qualitative study of work organization in the U.S. fresh tomato industry investigates how work processes and management structures impact tomato workers' occupational health. Methods : After conducting literature review and key informant interviews, semi-structured interviews and focus groups were conducted with 36 individuals with experience working in the U.S. fresh tomato industry. Interviews and focus groups were audio-recorded, transcribed, coded, and analyzed using a modified grounded theory approach. Results : These data indicate that participants endured income insecurity and hazardous supervisory practices, including wage theft, retaliation, intimidation, and humiliation, that put them at risk of preventable illness and injury. Support from workers' organizations and health-conscious supervisory practices helped mitigate some of these occupational hazards. Conclusion : Participants' adverse work experiences may be considered sequelae of workers' lack of job control and positions of socioeconomic structural vulnerability. Other aspects of tomato work organization, including health-conscious supervisory practices and the involvement of workers' organizations, indicate that modifying work organization to better safeguard health is possible. Such modifications present compelling opportunities for employers, employees, organizations, community and government leaders, and health care professionals to help create healthier occupational environments for tomato workers.